A bioanalytical strategy utilizing dried blood spot sampling and LC–MS/MS in discovery toxicology studies. (May 2012) - Discenza, Lorell; Obermeier, Mary T; Westhouse, Richard; Olah, Timothy V; D'Arienzo, Celia J
Background & Method: The small sample volumes characteristic to dried blood spot (DBS) sampling enabled us to right-shift the linear dynamic range of an LC–MS/MS plasma assay tenfold and eliminate the need for extensive sample dilution in support of three discovery toxicology studies in which both plasma and DBS samples were collected. With the right-shifted DBS assay range, no DBS study samples required dilution, while all of the plasma samples were diluted 5–50-fold.Results: DBS standard curves from 78–80, 000 nM were linear, the performance of the curve and QC samples was within acceptable discovery-assay criteria and individual plasma and DBS data were comparable. Linear correlations of Cmax and AUC derived from DBS and plasma data resulted in R 2 > 0.9.Conclusion: This bioanalytical strategy represents a benefit to the bioanalyst that can expedite the return of data and minimize the potential for error and variability that can result from extensive dilutions of study samples.